The body as capital : masculinities in contemporary Latin American fiction - Venkatesh, Vinodh (Tucson : The University of Arizona Press, 2015)
"The book analyzes the notion of the male body as a dialogic site of enunciation, arguing that the writing of masculinities is a project centering socioeconomic and political concerns, anxieties, and paradigms on the male anatomy and on masculinities presented in fiction, forging a new path in the critical debates over gender and sexuality in Latin American writing"--Provided by publisher.
Includes bibliographical references (pages 171-179) and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Masculinity in literature; Latin American literature -- History and criticism; Human body in literature; Sex role in literature; Electronic books